2019
DOI: 10.1136/bcr-2019-230732
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent colonic intussusception due to a lipoma of the transverse colon at the background of congenital dolichocolon and chronic constipation

Abstract: Colonic intussusception caused by benign tumour in adults is uncommon condition. Lipoma as benign tumour arises from submucosal layer of gastrointestinal tract and derives from mature adypocytes. It is usually small asymptomatic lesion and reveals during colonoscopy, CT, surgery or autopsy accidentally. However, in cases with large size it may cause abdominal pain, constipation, diarrhoea, anaemia, bleeding or intussusceptions. We present a 52-year-old female patient with colonic intussusception caused by lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Question deserves to be kept in mind, as to whether recurrence of abdominal pain in patients could be associated with episodes of intussusception, since pain is the most frequent symptom[ 2 ]. Constipation itself might be involved in colonic intussusception[ 18 ] but its contribution in this case remains difficult to assess. Because of the presence of a lesion in the colon, even benign, surgical intervention remained indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Question deserves to be kept in mind, as to whether recurrence of abdominal pain in patients could be associated with episodes of intussusception, since pain is the most frequent symptom[ 2 ]. Constipation itself might be involved in colonic intussusception[ 18 ] but its contribution in this case remains difficult to assess. Because of the presence of a lesion in the colon, even benign, surgical intervention remained indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we could safely perform laparoscopy-assisted surgery. Siamionava et al [ 34 ] reported a case of colon lipoma with several episodes of bowel obstruction, in which elective surgery was performed after conservative treatment. Nissen et al .…”
Section: Discussionmentioning
confidence: 99%